Heat transfer effects on the performance of an air-standard irreversible dual cycle - Ust, Yasin; Sahin, Bahri; Kayadelen, Hasan Kayhan; Gonca, Guven (INDERSCIENCE ENTERPRISES LTD, 2013)
The objective of this study is to analyse the effects of heat transfer loss and internal irreversibilites, resulting from adiabatic processes, on an irreversible diesel heat engine. Thermodynamic optimisation has been carried out based on the Maximum Power (MP), Maximum Thermal Efficiency (MEF) and Maximum mean Effective Pressure (MEP) criteria for the dual cycle. Power output, thermal efficiency and mean effective pressure are obtained by introducing variable compression ratio, inlet temperature, combustion and heat transfer constants, and compression and expansion efficiencies. Optimal performance and design parameters of the dual cycle are obtained numerically for the MP, MEF and MEP conditions. The optimal compression ratio and pressure ratio at MEP conditions are compared with those results obtained by using the MP and MEF criteria for different constants of heat transfer and combustion in the characteristic grid curves. The results obtained in this paper may provide a guide to the performance and improvement of practical diesel engines.
Keywords: dual cycle; optimal performance; performance analysis; thermodynamic optimisation; combustion; heat transfer; VARIABLE SPECIFIC-HEATS; ENTROPY GENERATION MINIMIZATION; ENDOREVERSIBLE OTTO CYCLE; THERMODYNAMIC SYSTEMS; WORKING FLUID; OPTIMAL PATHS; FUELS ENERGY; OPTIMIZATION; POWER; Engineering; Transportation